El reto inmunológico con promastigotes de Leishmania (Viannia) panamensis en Galleria mellonella modula cambios en los perfiles de expresión de proteínas de bajo peso molecular (2017)
ABSTRACT: The Leishmania parasite is responsible for several diseases that affect humans and animals in more than 95 countries including Colombia. Despite the known toxicity shown by current drugs such as Glucantime or Amphotericin B, they are still used as treatments against the parasite. Natural antimicrobial peptides (AMPs) are considered promising agents for use against a broad spectrum of infectious diseases, they are considered promising and non-toxic therapeutic agents. AMPs are part of the immune response of organisms such as insects, from where they have been isolated and shown to have antibacterial and antifungal activity. Galleria mellonella moths express a broad repertoire of peptides in response to challenges with different organisms. This suggests an alternative for obtaining peptides with anti- parasitic activity. This study was based on the immunological challenge induced in Galleria mellonella larvae with Leishmania (viannia) panamensis promastigotes, with the goal of isolating a peptide fraction with antiparasitic activity. Non-challenged hemolymph and hemolymph obtained from the immunization with PBS and parasites were compared. Free hemocyte hemolymph from each treatment was analyzed by two-dimensional electrophoresis (2D gel). Furthermore, hemolymphs were fractionated by RP-HPLC. 2D gel analysis identified 4 spots in challenged hemolymph and 3 spots in PBS hemolymph. These spots were not present in the control hemolymph. On the other hand, fractions from RP-HPLC of challenged hemolymph showed more antileishmania activity in comparison to the same fractions from the hemolymph control. This study may provide the basis for new antileishmanial peptides.